Tailoring the low-density polyethylene - thermoplastic starch composites using cellulose nanocrystals and compatibilizer - Alireza Kaboorani (Elsevier, 2021)
In this study, the mechanical, barrier, and biodegradation characteristics of low-density polyethylene (LDPE) and thermoplastic starch (TPS) composites with and without compatibilizer (CA), cellulose nanocrystal (CNCs), and their combination was investigated and compared. The results revealed the LDPE/TPS composites containing CNCs and CA exhibited higher mechanical and vapor barrier and lower water adsorption properties than LDPE/TPS composites without CA and CNCs. The combined addition of CA and CNCs resulted in homogenous composites with the highest tensile and barrier characteristics. The added CNCs led to better interaction between the LDPE and TPS phases, indicating CA could be replaced by CNCs without scarifying the performance of composites. Biodegradation investigation showed the addition of CNCs improved the resistance of LDPE/TPS composites towards biotic attacks. Improving the properties by CNCs addition could be an effective and sustainable method for reducing global utilization of LDPE in the production of LDPE/TPS composites.